Effectiveness of water hyacinth compost and N, P, K, S fertilizer on S-available, S uptake, protein content, and yield of shallot in Inceptisols from Jatinangor - Sofyan, Emma Trinurani; Gumelar, Fajar Akbar; Yuniarti, Anni; Joy, Benny; Wicaksono, Fiky Yulianto (Universitas Padjadjaran, 2023)
. Water hyacinth (Eichhornia crassipes) is a source of organic matter that can be used as compost to improve the soil quality and productivity of shallots. Shallots are horticultural commodities that have various benefits. Inceptisol soils dominate Indonesia, with an area of 37.5% of Indonesia's land area but have low soil fertility. Soil fertility can be increased by optimal fertilization. This experiment aimed to determine the dose of water hyacinth compost and nitrogen (N), phosphor (P), potassium (K), sulfur (S) fertilizer which gave the best effect on increasing available S, S uptake, protein content, and yield of shallots. The experiment was conducted from July to October 2021 at the Experimental Garden of the Laboratory of Soil Chemistry and Plant Nutrition, Faculty of Agriculture, Universitas Padjadjaran, Jatinangor. The experiment used a Randomized Block Design, consisting of seven treatments repeated four times. The recommended fertilizer doses used are 200 kg Urea, 500 kg ZA, 300 kg SP-36, and 200 kg KCl. The compost used was water hyacinth compost at a 25 t/ha dose. The results of this experiment showed that the treatment of ¾ compost + ¾ doses of N, P, K, and S was the best in increasing available S (26.79 mg kg-1), S uptake (7.03 mg/plant), protein content (0.95%), colors and shallot yield (number of tubers, fresh weight, and dry weight) on Inceptisols from Jatinangor.